2018
DOI: 10.1055/a-0643-4739
|View full text |Cite
|
Sign up to set email alerts
|

Altered Glucose Uptake in Muscle, Visceral Adipose Tissue, and Brain Predict Whole-Body Insulin Resistance and may Contribute to the Development of Type 2 Diabetes: A Combined PET/MR Study

Abstract: We assessed glucose uptake in different tissues in type 2 diabetes (T2D), prediabetes, and control subjects to elucidate its impact in the development of whole-body insulin resistance and T2D. Thirteen T2D, 12 prediabetes, and 10 control subjects, matched for age and BMI, underwent OGTT and abdominal subcutaneous adipose tissue (SAT) biopsies. Integrated whole-body F-FDG PET and MRI were performed during a hyperinsulinemic euglycemic clamp to asses glucose uptake rate (MRglu) in several tissues. MRglu in skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 39 publications
2
29
1
Order By: Relevance
“…However, in individuals with impaired fasting glucose (IGF), the brain glucose utilization increases in response to insulin infusion suggesting that the brain glucose metabolism is disturbed even in IFG (Hirvonen et al, 2011). Using whole-body [ 18 F]FDG PET and hyperinsulinemic euglycemic clamp, it was recently demonstrated that the brain glucose utilization is increased in patients with T2D (Boersma et al, 2018). In contrast, the authors found that the glucose utilization was decreased in skeletal muscle, visceral- and adipose tissue, and the liver in patients with T2D (Boersma et al, 2018).…”
Section: In Vivo Imaging Of Glucose- and Lipid Metabolism In Type 2 Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in individuals with impaired fasting glucose (IGF), the brain glucose utilization increases in response to insulin infusion suggesting that the brain glucose metabolism is disturbed even in IFG (Hirvonen et al, 2011). Using whole-body [ 18 F]FDG PET and hyperinsulinemic euglycemic clamp, it was recently demonstrated that the brain glucose utilization is increased in patients with T2D (Boersma et al, 2018). In contrast, the authors found that the glucose utilization was decreased in skeletal muscle, visceral- and adipose tissue, and the liver in patients with T2D (Boersma et al, 2018).…”
Section: In Vivo Imaging Of Glucose- and Lipid Metabolism In Type 2 Dmentioning
confidence: 99%
“…Using whole-body [ 18 F]FDG PET and hyperinsulinemic euglycemic clamp, it was recently demonstrated that the brain glucose utilization is increased in patients with T2D (Boersma et al, 2018). In contrast, the authors found that the glucose utilization was decreased in skeletal muscle, visceral- and adipose tissue, and the liver in patients with T2D (Boersma et al, 2018).…”
Section: In Vivo Imaging Of Glucose- and Lipid Metabolism In Type 2 Dmentioning
confidence: 99%
“…Semi-synthetic human insulin (Actrapid, Novo Nordisk, Copenhagen, Denmark) was infused at 56 mU/m 2 body surface/min and a variable glucose infusion (200 mg/ml) was adjusted to maintain a stable plasma glucose level of 5.6 mmol/l. The data collection has previously been described in more detail 18,19 . pet/MR imaging.…”
Section: Methodsmentioning
confidence: 99%
“…injection of 4 MBq [ 18 F]FDG/kg bodyweight was used. A 10 min dynamic PET scan of the thorax was collected to capture early tracer dynamics of [ 18 F]FDG 13,18 . After this, five whole-body PET scans (from head to toe) were acquired.…”
Section: Methodsmentioning
confidence: 99%
“…We compared Eq. (1) parameters with diffusion coefficients measured using UV imaging in agarose hydrogels that is used for mimicking subcutaneous tissues 27,28 . Experimental results of insulin diffusion coefficients in different medium conditions ranges between 0.8–2.0 (m 2 /s).…”
Section: Section 1: Algorithms Design and Set Up Requirementsmentioning
confidence: 99%